Gambling problems in bipolar disorder in the UK: Prevalence and distribution. (October 2015) - Jones, Lisa; Metcalf, Alice; Gordon-Smith, Katherine; Forty, Liz; Perry, Amy; Lloyd, Joanne; Geddes, John R.; Goodwin, Guy M.; Jones, Ian; Craddock, Nick; Rogers, Robert D.
Abstract : Background: North American studies show bipolar disorder is associated with elevated rates of problem gambling; however, little is known about rates in the different presentations of bipolar illness. Aims: To determine the prevalence and distribution of problem gambling in people with bipolar disorder in the UK. Method: The Problem Gambling Severity Index was used to measure gambling problems in 635 participants with bipolar disorder. Results: Moderate to severe gambling problems were four times higher in people with bipolar disorder than in the general population, and were associated with type 2 disorder (OR = 1.74, P = 0.036), history of suicidal ideation or attempt (OR = 3.44, P = 0.02) and rapid cycling (OR = 2.63, P = 0.008). Conclusions: Approximately 1 in 10 patients with bipolar disorder may be at moderate to severe risk of problem gambling, possibly associated with suicidal behaviour and a rapid cycling course. Elevated rates of gambling problems in type 2 disorder highlight the probable significance of modest but unstable mood disturbance in the development and maintenance of such problems.